The aesthetics of the artistic image in the enthusiasm of Abi Tammam The door of enthusiasm is a model (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research studies the aesthetics of the artistic image in the enthusiasm of Abi Tammam (the chapter of enthusiasm). The aesthetic of the poetic impression of the recipient, which reflects the goal that Abu Tammam wanted to convey to him, and which shows the reason why Abu Tammam wrote the book “The enthusiasm”